Determinants of Adolescent Sexual Behavior in Cirebon Regency - Ayu Ashari; Ria Yulianti Triwahyuningsih; Fika Nurul Hidayah (HM Publisher, 2022)
Introduction: This study aims to determine what factors are associated with adolescent sexual behavior in the district. Methods: This study uses analytical methods. The type of research used is quantitative research with a cross-sectional approach, statistical tests, and data processing using Partial Least Square (SmartPLS 3.0). Results: The results of the study show that (1) Information media has a significant influence on knowledge; (2) Information media and the role of parents have a significant influence on the dating status of adolescents; (3) Information media, peer influence, knowledge, and demographic status have a significant influence on adolescent attitudes; (4) The influence of peers, demographic status, and courtship status have a significant influence on adolescent sexual behavior; (5) 10.88% of sexual behavior is influenced by factors in this study, while 89.12% of sexual behavior is influenced by other factors outside this study. Conclusion: Information media has a significant influence on knowledge. The influence of peers, demographic status, and dating status has a significant influence on adolescent sexual behavior.